2007
DOI: 10.1007/s00180-007-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the bandwidth choice for kernel density estimates

Abstract: Kernel, Smoothing parameter, Iterative method, 62G07, 30C40,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…According to Horova et al (2008), this equation (2.1) does not have a general closed-form expression, so we result to its asymptotic approximation (AMISE). Hence (2.1) could be factored as;…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Horova et al (2008), this equation (2.1) does not have a general closed-form expression, so we result to its asymptotic approximation (AMISE). Hence (2.1) could be factored as;…”
Section: Literature Reviewmentioning
confidence: 96%
“…We observed that the quality of the AMISE to the MISE is given according to Horova et al (2008) . The big O notation is applied element-wise.…”
mentioning
confidence: 99%
“…The optimal smoothing parameter is defined to be the value of h that minimizes the error between the estimated pdf and the true pdf. The most common metric to represent this error is the mean integrated squared error (MISE) which is expressed as [12]…”
Section: Smoothing Parameter Selectionmentioning
confidence: 99%
“…Hazard of death was computed on the same time scale. In the smoothing procedure used to compute the hazard [15], the smoothing bandwidth was optimized by the method proposed by Harová and Zelinka [16].…”
Section: Historical Background Of the National Registry Of Patients Wmentioning
confidence: 99%